2010
DOI: 10.1097/sla.0b013e3181b76557
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Low Platelet Count is Associated With Delayed Liver Function Recovery After Partial Liver Resection

Abstract: After partial liver resection, a low platelet count is an independent predictor of delayed postoperative liver function recovery and is associated with increased risk of postoperative mortality. These clinical findings are in accordance with the accumulating evidence from experimental studies, indicating that platelets play a critical role in liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 27 publications
8
116
1
1
Order By: Relevance
“…Murata et al reported that platelets promote liver regeneration in the early period in a murine model [46]. Furthermore, Alkozai et al reported that a low platelet count immediately after partial hepatectomy was associated with delayed recovery of liver function [47]. Based on these results, platelet count appears to be a sensitive marker with respect to liver regeneration or functional recovery after liver stress or injury.…”
Section: Discussionmentioning
confidence: 99%
“…Murata et al reported that platelets promote liver regeneration in the early period in a murine model [46]. Furthermore, Alkozai et al reported that a low platelet count immediately after partial hepatectomy was associated with delayed recovery of liver function [47]. Based on these results, platelet count appears to be a sensitive marker with respect to liver regeneration or functional recovery after liver stress or injury.…”
Section: Discussionmentioning
confidence: 99%
“…), was used according to the recommendations of the International Federation of Clinical Chemistry (IFCC). 3,4 For statistical analyses, mouse models were summarized as toxic/chemically induced (4-and 7-days LCA-fed, and 1-, 4-, and 8-weeks DDCfed mice), genetically induced (8-weeks-and 4-months-old…”
Section: Serum Alkaline Phosphatase Levels Accurately Reflect Cholestmentioning
confidence: 99%
“…Various animal experiments in pigs, mice and rats confirmed the promotive effect of platelets after hepatectomy [14]. Delayed liver function after liver surgery for colorectal metastases in non-cirrhotic patients with postoperative low platelet counts has been described [15].…”
Section: Introductionmentioning
confidence: 92%